ANALISIS PENGEMBANGAN WEBSITE www.jogjakota.go.id DALAM PENYELENGGARAAN E-GOVERNMENT DI PEMERINTAHAN KOTA YOGYAKARTA - Anjarini, Annisa Kurnia; Dwimawanti, Ida Hayu (Journal of Public Policy and Management Review, 2018)
The development of Yogyakarta City official website held in attempt to the egovernment of a Yogyakarta City has objective to ease services information through the use of information technology to Yogyakarta cityzen, private, and the other government. The research problem is: How the analysis of the development of website in e-government organization at Yogyakarta City? and what are motivation factor and the obstacles of the website development in Yogyakarta City?. The purpose of this study to describe and analyze how the development of website and to describe the obstacles faced by the development of e-government in the Yogyakarta City. To answer the problem and the research objectives using successful elements of e-government development in the Harvard JFK School of Government, namely : support, capacity, and value. This research uses descriptive qualitative method. This study using interviews, observation, and documentation as well as triangulation associated with the development of electronic government in Yogyakarta City. The results showed that the motivation factors of website development in Yogyakarta city are support because of Yogyakarta City has a regulation of e-government that can be the commitment of Yogyakarta’s government and capacity because of the preparation and development from human resource and financial resource were done. The obstacle is value elemen, because of Yogyakarta citizen doesn’t know yet about the using of Yogyakarta official website caused by the minimum knowledge of technology information, the website just shows information service so the citizen to lose their motivation to accses, and the lack of reciprocal from citizen to government that can be post in Yogyakarta official website.